The impact of diabetes mellitus type 1 on male fertility: Systematic review and meta‐analysis. (22nd December 2021) - Facondo, Paolo; Di Lodovico, Elena; Delbarba, Andrea; Anelli, Valentina; Pezzaioli, Letizia Chiara; Filippini, Erica; Cappelli, Carlo; Corona, Giovanni; Ferlin, Alberto
Abstract: Background: Some evidence suggests that diabetes mellitus type 1 (DM1) could affect male fertility, gonadal axis, semen parameters, and spermatogenesis because of effects of hyperglycemia and insulin deficiency. Anyhow, the exact impact of DM1 on male fertility is unclear. Objectives: To review the studies evaluating paternity rate, male gonadal axis, and semen parameters in men with DM1. Materials and methods: A review of relevant literature from January 1980 to December 2020 was performed. Only studies published in English reporting data on fatherhood (rate of children by natural fertility), hormonal and seminal parameters were included. Out of 14 retrieved articles, the eight studies evaluating semen parameters were meta‐analyzed. Results: The rate of children (four studies) was lower than controls among men affected by DM1, especially in men with a longer duration of disease. The data of gonadal hormonal profile in DM1 men (six studies) are very heterogeneous and a neutral effect of DM1 or a condition of subclinical hypogonadism could not be concluded. Meta‐analysis showed that men with DM1 ( n = 380), compared with controls ( n = 434), have significantly lower normal sperm morphology [‐0.36% (‐0.66; ‐0.06), p < 0.05, six studies] and sperm progressive motility [33.62% (‐39.13; ‐28.11), p < 0.001, two studies] and a trend toward a lower seminal volume [‐0.51 (‐1.03; 0.02), p = 0.06, eight studies], without difference in total sperm count and concentration. Data on scrotal ultrasound and sperm DNA fragmentation are too few. No study evaluated other factors of male infertility, such as transrectal ultrasound, semen infections, sperm auto‐antibodies, and retrograde ejaculation. Discussion: DM1 might impair male fertility and testis functions (endocrine, spermatogenesis), but definition of its actual impact needs further studies. Conclusion: Men with DM1 should be evaluated with a complete hormonal, seminal, and ultrasound workup to better define their fertility potential and need for follow up of testis functions.